(3ZGjI GdeQGe aj QLGd GdoHNGQj Edi SjO GdCfGes - (3eMeO Hf OGhO Hf eMeO, TeS GdOjf CHh YHO Gddg , GdHGRdj,J (B925 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj QaY efGQ GdMb HHYKg GdfHj hQMe GdNdb HEQSGd GdfHj GdCej s
(3BNQgG (B:s
(3gPG BNQ GdLRA GdChd ef ZGjI GdeQGe aj QLGd GdoHNGQj Edi SjO GdCfGe MTQfG Gddg JYGdi aj ReQJge jJdhg GdLRA GdKGfj(B: (3YHOGdCYdi, Efg hdj GdELGHI s
(3GfXQ Qbe (B350 (3JGQjNs
(3fSNI KGfjI hbO JZjQ Gdbde ajgG eQGQkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B120 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B297s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B99 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B117 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B300 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs